Hubungan Antara School Wellbeing dengan Motivasi Belajar Pada Siswa SMA Y di Makassar - Novita Maulidya Jalal (Universitas Negeri Makassar, 2022)
Schools have an important role in the development of the mindset and mentality of students. Students who feel prosperous studying at school can foster their enthusiasm for learning. This study aims to determine the relationship between well-being at school or school well-being with learning motivation in high school students in Makassar. The research method used in this study is a quantitative method by conducting the Spearman correlation test. Sampling used a purposive sampling technique, where the criteria for the subjects in this study were students of SMA Negeri Y Makassar and aged 15-18 years. Data collection was carried out using a questionnaire scale via Google Form. The distribution of the scale via Whatsapp social media to students of SMA Negeri Y Makassar on 21 – 24 May 2022. The results of this study show that school well-being has a correlation of 0.696 with learning motivation in SMA Negeri Y Makassar and a significance value of 0.000 <0.05. Thus it can be concluded that there is a relationship between school wellbeing and learning motivation in students at SMA Negeri Y Makassar. The implication of this research is that it is hoped that students will gain positive experiences while studying at school which is manifested in positive and prosperous assessments of students towards their schools or school wellbeing so that students can participate in the learning process happily and prosperously.